National study of microphthalmia, anophthalmia, and coloboma (MAC) in Scotland: investigation of genetic aetiology. Issue 1 (1st January 2002) - Morrison, D; FitzPatrick, D; Hanson, I; Williamson, K; van Heyningen, V; Fleck, B; Jones, I; Chalmers, J; Campbell, H
Abstract : We report an epidemiological and genetic study attempting complete ascertainment of subjects with microphthalmia, anophthalmia, and coloboma (MAC) born in Scotland during a 16 year period beginning on 1 January 1981. A total of 198 cases were confirmed giving a minimum live birth prevalence of 19 per 100 000. One hundred and twenty-two MAC cases (61.6%) from 115 different families were clinically examined and detailed pregnancy, medical, and family histories obtained. A simple, rational, and apparently robust classification of the eye phenotype was developed based on the presence or absence of a defect in closure of the optic (choroidal) fissure. A total of 85/122 (69.7%) of cases had optic fissure closure defects (OFCD), 12/122 (9.8%) had non-OFCD, and 25/122 (20.5%) had defects that were unclassifiable owing to the severity of the corneal or anterior chamber abnormality. Segregation analysis assuming single and multiple incomplete ascertainment, respectively, returned a sib recurrence risk of 6% and 10% in the whole group and 8.1% and 13.3% in the OFCD subgroup. Significant recurrence risks were found in both unilateral and bilateral disease. In four families, one parent had an OFCD, two of which were new diagnoses in asymptomatic subjects. All recurrences in first degree relatives occurred in the OFCD group with a single first cousin recurrence seen in the non-OFCD group. A total of 84/122 of the MAC cases were screened for mutations in the coding regions of PAX6, CHX10, and SIX3. No pathogenic mutations were identified in the OFCD cases. A single PAX6 homeodomain missense mutation was identified in a subject with partial aniridia that had been initially misclassified as coloboma.